2015
DOI: 10.5130/ccs.v7i3.4473
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Progress : Human Rights and International Students in Australia

Abstract: The rapid growth in international student numbers in Australia in the first decade of the 2000s was accompanied by a series of public crises. The most important of these was the outbreak in Melbourne Victoria and elsewhere of physical attacks on the students. Investigations at the time also pointed to cases of gross exploitation, an array of threats that severely compromised their human rights. This paper reviews and pursues the outcomes of a report prepared by the authors in 2010 for Universities Australia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…At best, under the neoliberal ethos, both international students and their host HEIs begin to view their relationship as one between customer/consumer on one hand and service-provider on the other. This arguably impoverishes the educational/pedagogical relationship by reducing it to a transactional relation entailing mainly provider “duties” and “consumer rights” (Jakubowicz & Monani, 2010; Ramia et al, 2013; Tran & Nyland, 2018; Waters, 2018b). At its worst, the neoliberalization of ISM could bring up controversial questions that unsettle some of the social ideals about education as well as political values said to be fundamental to liberal democratic societies.…”
Section: Critical Perspectives Underpinning Ism Ethics and Politics: mentioning
confidence: 99%
See 1 more Smart Citation
“…At best, under the neoliberal ethos, both international students and their host HEIs begin to view their relationship as one between customer/consumer on one hand and service-provider on the other. This arguably impoverishes the educational/pedagogical relationship by reducing it to a transactional relation entailing mainly provider “duties” and “consumer rights” (Jakubowicz & Monani, 2010; Ramia et al, 2013; Tran & Nyland, 2018; Waters, 2018b). At its worst, the neoliberalization of ISM could bring up controversial questions that unsettle some of the social ideals about education as well as political values said to be fundamental to liberal democratic societies.…”
Section: Critical Perspectives Underpinning Ism Ethics and Politics: mentioning
confidence: 99%
“…Perhaps reflecting the neoliberal hegemony in international higher education, scholars found that student rights are prevailingly conceptualized in terms of consumer rights, and such a notion appears to be strongly internalized by international students themselves (Jakubowicz & Monani, 2010; Tran & Nyland, 2018). At the core of this neoliberal consumerist understanding of international student rights is education rights , which Tran and Nyland (2018) define as “the right to be provided with high-quality teaching and learning and with adequate resources to support learning” (p. 130).…”
Section: Elements Of a Framework For Ism Ethics And Politics: Key Actmentioning
confidence: 99%